Comparison of Complications between Forceps and Injector Delivery for Acrylic Multipiece IOL - Lubna Siddiq, Muhammad Moin, Asif Manzoor (Pakistan Journal of Ophthalmology, 2017)
Purpose: To compare complications between forceps and injector delivery for Acrylic multipiece intraocular lens (IOL) in phacoemulsification. Study Design: Randomized Clinical Trial. Place & Duration of Study: Yaqin Vision Eye center from October 2002 to June, 2017. Material and Methods:All patients undergoing routine phacoemulsification with implantation of foldable acrylic multipiece IOL (Acrysof MA60 AC, Alcon, USA) were included in the study. The patients were divided into two groups according to the method of insertion of the IOL. Group A included patients undergoing foldable implantation with forceps while group B included patients in which injector was use to implant the IOL. Total 820 patients were included in study. Group A included 408(49.76%) patients and 412 (50.24%) patients were included in Group B. Patients undergoing phaco trabeculectomy, phaco vitrectomy, lensectomy and implantation of all other types of IOL, were excluded from the study. Any complications arising during insertion of IOL were recorded in the electronic records of the patients. Results were analyzed using SPSS version 20. Results: Out of 820 patients Group A included 408 patients with average age of 63 ±12.2 yrs with 189 (46.32%) males and 219 (53.68%) females while group B included 412patients with average age of 60 ±16.4 yrs with 182 (44.17%) males and 230 (55.83%) females. In group A there were 392 (96 %) IOLs implanted in the bag and 16 (4%) in the sulcus. In group B there were 396 (96%) IOLs implanted in the bag and 16 (4%) in the sulcus. Forceps delivery needed enlargement of incision to 3.5 mm for IOL insertion with no insertion related complication. While Injector delivery needed only 3.0 mm enlargement of wound with few injectors related complications. These included optic and haptic damage 2(0.48%), flipping of IOL back to front 4(0.97%) and posterior capsular rent (PCR) with haptic 1(0.24%) while injecting. Injector insertion allowed insertion of IOL in bag in cases of small PCR due to deep and stable chamber during IOL insertion compared to forceps delivery.These complications with injectors happened in early transition from forceps to injector technique. Conclusion: Delivery of multipiece IOL with injector has more complications compared to forceps delivery. Therefore practice of IOL insertion with injector in wet lab is recommended before switching to this technique. Keywords: Phacoemulsification, Acrylic intraocular lens, Injector, Forceps.